Clinical outcomes from antihypertensive therapies in moderate or severe aortic stenosis: a systematic review and meta-analysis. (25th November 2020) - Sen, J; Chung, E; Neil, C; Marwick, T
Abstract: Background: Hypertension can negatively affect prognosis in moderate or severe aortic stenosis (AS), but antihypertensive therapy (AHT) is often avoided due to possible deleterious effects such as reduced coronary perfusion, left ventricular dysfunction and haemodynamic compromise. Purpose: We systematically assessed and compared clinical outcomes in adults with moderate or severe AS treated with and without AHT. Methods: Two independent reviewers performed screening, data extraction and risk of bias assessments from a systematic search of the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and grey literature without language restrictions up to September 9, 2019. Conflicts were resolved by the third reviewer. Outcomes of interest included mortality, left ventricular (LV) mass index, systolic blood pressure, diastolic blood pressure, and LV ejection fraction. Meta-analysis with pooled effect sizes using random-effects model, were estimated in R. Results: Of 3, 024 citations, 30 studies (26, 224 patients) were included in the qualitative synthesis and 23 studies in meta-analysis. AHT was associated with favourable clinical outcomes and was well tolerated. AHT was associated with lower risk of all-cause mortality (Risk Ratio (RR)=0.69, 95% CI: 0.53–0.90, p=0.01, Figure). The effect size appears to differ with type of aortic valve replacement (AVR). AHT was associated with lower risk of acute kidney injury post-transcatheter AVR (RR=0.13, 95% CI:0.05–0.35, p=0.007). Favourable outcomes such as improved haemodynamic and echocardiographic parameters were demonstrated in some studies, but when pooled in meta-analysis, the differences did not reach statistical significance. However, heterogeneity was significant across studies. Conclusion: This is the first systematic review and meta-analysis to demonstrate that AHT is safe and has a clinical benefit in patients with advanced stages of AS with significant improvement in survival or reduction in mortality without haemodynamic compromise. Further studies are required to determine the best AHT for patients with moderate or severe AS. Funding Acknowledgement: Type of funding source: None